Revisión de literatura sobre las principales patologías podales que afectan a la ganadería bovina lechera en Colombia, América latina y el Caribe (2021)
Dairy farming in Latin American and Caribbean countries is on the rise, according to FEPALE, which is the organization that brings together the dairy sector in the Americas, Latin America contributes between 10-15% of world production, due to the constant demand for dairy products. milk for human consumption, which is economically very favorable for these countries. Therefore, the objective of this study is to collect and document which are the foot pathologies and risk factors that are most preceded by the dairy union, because they lead to economic losses for large producers, but even more so for small producers, who with only being affected an animal already leads to very serious losses. After conducting the literature search on foot pathologies, several important determinants could be reached, qualities are the points that remain strong, others in decline and some that can begin to be implemented to improve in the area of buiatrics in dairy. A first point was the high percentage (65%) of dairy cattle animals that present some complication of foot origin and one (37%) present lameness. Another point is that most of the information collected was found from scientific articles in countries such as Argentina, Brazil, Chile, Colombia, Cuba and other countries in the American region. It is also evident that the prevalence of certain foot pathologies changes between countries; For example, in Brazil, the most prevalent pathologies are sole ulcers and white line disease, while in Argentina, interdigital dermatitis and chronic laminitis prevail. Something evident within the literature review study was to find a decrease of approximately 60% of reports on foot pathologies in the Latin American and Caribbean region. The environmental or hygiene factors of the establishments are also important for the progression of these pathologies, in addition to inadequate nutrition, for which early detection helps us to establish an adequate therapeutic management in the affected vacations, health and hygiene are measures priority.